Immunotherapy for bilateral multiple ground glass opacities: An exploratory study for synchronous multiple primary lung cancer - Xu, Lin; Shi, Meiqi; Wang, Siwei; Li, Ming; Yin, Wenda; Zhang, Jingyuan; Zhu, Jun; Jiang, Feng; Xia, Wenjia; Qiu, Ninglei; Zhang, Zhi; Huang, Jianfeng; et al. (Frontiers in Immunology, 2022)
Background Bilateral multiple ground glass opacities (GGOs) are observed in quite a part of patients with early-stage lung adenocarcinoma. For this so-called synchronous multiple primary lung cancer (sMPLC), targeting immune checkpoint is a favorable option in addition to surgical resection. The purpose of this study is to reveal the safety and efficacy of performing immune checkpoint inhibitors (ICIs) on patients with sMPLC and to explore the biomarkers of the efficacy. Methods A total of 21 patients with sMPLC were enrolled and all included cases were pathologically confirmed adenocarcinoma after conducting surgical treatment for unilateral GGOs. ICIs of Sintilimab were then used to target programmed death 1 (200mg i.v., Q3W) for up to 10 cycles. Seven patients of them received the other surgery for contralateral GGOs, and multiomics assessments, including neoantigens, somatic mutations, and methylated loci, were further performed to investigate potential biomarkers. Results Grade 1 or 2 treatment-related adverse events (AEs) occurred in most of the patients (12/21, 57.1%), and one subject withdrawn for grade 3 AEs. For the seven patients underwent twice surgeries, twelve and thirteen GGOs were achieved before and after the use of ICIs separately, and a favorable efficacy was observed among six lesions after immunotherapy (> 50% pathologic tumor regression). Tumor infiltration T-cell and B-cell were further shown to be associated with the biological activity of ICIs. According to mechanism-based multiomics analyses, MUC19- and PCDHB5- mutations were indicated to correlate with a favorable prognosis of sMPLC underwent immunotherapy, and our results suggested that immunogenetic mutation and associated promoter methylation could provide a quantitative explanation for the pathologic response of GGOs. Conclusion Our study provides evidence that the use of ICIs contributed favorable efficacy and safety to patients with sMPLC. Immune infiltration and immunogenic biomarkers are revealed to be implications of performing ICIs on sMPLC. These preliminary findings exhibit the prospects in performing neoadjuvant or adjuvant immunotherapies on patients with sMPLC. Clinical Trial Registration https://www.chictr.org.cn/showproj.aspx?proj=36878, identifier ChiCTR1900022159.